Dialkyl Diazomalonates in Transition-Metal-Free, Thermally Promoted, Diastereoselective Wolff β-Lactam Synthesis - Synofzik, Judith; Bakulina, Olga; Dar’in, Dmitry; Kantin, Grigory; Krasavin, Mikhail (Synlett, 2020)
Metal-free, thermally promoted synthesis of 3-alkoxy-3-alkoxycarbonyl-2-azetidinones via the Wolff-Staudinger β-lactam synthesis using dialkyl diazomalonates is described. The reaction appears fairly general and delivers only one diastereomer.
Keywords: β-lactam; diazomalonates; Wolff rearrangement; metal-free; thermal